Meta-analisis Pengaruh Metode Gasing Pada Pembelajaran Matematika SD dalam Meningkatkan Hasil Belajar Siswa - Ari Wicaksono Wibowo; Gustina Dwi Suryaningrum; Nila Ariana Ristianti; Priti Agustin; Putri Prasetyaningtyas (Universitas Muhammadiyah Enrekang, 2022)
The background of this research is the low learning outcomes in Mathematics. Because mathematics is considered a difficult subject to understand, and the method given only uses formulas. So that students mostly memorize formulas that make students bored so that learning becomes meaningless. This study aims to analyze the effect of using the gasing method on elementary mathematics learning in improving student learning outcomes. The method used in this study is a meta-analysis method. The research data was obtained by searching online journals through Google Scholar or Google Scholars with the search keywords